2005
DOI: 10.1007/s10350-005-0064-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Sildenafil Citrate on the Tonus of Isolated Dog Internal Anal Sphincter

Abstract: This experimental in vitro study showed that sildenafil citrate relaxes acetylcholine stimulated contractions of isolated dog internal anal sphincter. This may be of importance for raising the possibility that sildenafil cit-rate may have future potential in the treatment of chronic anal fissure. Further studies are needed for a conclusive decision on possible usefulness of sildenafil citrate in patients with chronic anal fissure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Anal tone was reduced by an average of 18% in less than 3 minutes. These findings have been corroborated in in vitro studies [176,177]. Currently there is no published work on whether phosphodiesterase-5 inhibitors can induce healing of fissures but this topic warrants further investigation.…”
Section: Phosphodiesterase-5 Inhibitorssupporting
confidence: 66%
“…Anal tone was reduced by an average of 18% in less than 3 minutes. These findings have been corroborated in in vitro studies [176,177]. Currently there is no published work on whether phosphodiesterase-5 inhibitors can induce healing of fissures but this topic warrants further investigation.…”
Section: Phosphodiesterase-5 Inhibitorssupporting
confidence: 66%
“…There are some trials focusing on new areas of use sildenafil, including chronic anal fissure [16,17], primary pulmonary hypertension [18], the increasing of retinal blood flow [19], and hypercontractile eosophageal motility disorders [20]. Eherer et al [21] reported that sildenafil reduced basal pressure and sphincter volume of the lower oesophageal sphincter.…”
Section: Discussionmentioning
confidence: 98%
“…Aygen et al. [75] showed that sildenafil relaxes acetylcholine stimulated contractions of isolated dog IAS. Torrabadella et al.…”
Section: Gastrointestinal Implicationsmentioning
confidence: 99%
“…Ballester et al [74] investigated the relaxant effects of sildenafil on isolated human IAS concluding that it relaxes the augmented tone of human IAS in vitro supporting its potential use in treating chronic anal fissure. Aygen et al [75] showed that sildenafil relaxes acetylcholine stimulated contractions of isolated dog IAS. Torrabadella et al [76] showed that topical 10% sildenafil was accompanied by significant reduction in anal sphincter pressure with average onset of action <3 minutes with maximum effect 1 minute later.…”
Section: Anal Fissurementioning
confidence: 99%